PENGARUH KETIDAKPUASAN KONSUMEN DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK HANDPHONE ANDROID DARI SAMSUNG KE OPPO (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN TERNATE) - Nurhidayanti N Lamani; Ida Hidayanti; Ibnu Sina Hi. Yusuf (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2020)
Objective: The purpose of this study was to determine the effectof Consumer dissatisfaction (the need to find variations and thetransfer of Android mobile brands from Samsung to OPPO)through Smartphone users of the Khairun ternate University ofEconomics and Business students, the number of researchsamples was 100 economic sample students in this study usingPurposive sampling and snowboil sampling.Methodology: The analytical method used is multiple linearregression analysis.Finding: H1 H2, and H3 accepted at the 5% confidence level.Conclusion: The results showed that (1) Partial dissatisfactionhad a significant effect on brand displacement in EconomicsStudents of Khairun University, Ternate, (2) Needs to findvariations had a positive and significant effect on branddisplacement on Economics Students of Khairun University ofTernate, and (3) Consumer Dissatisfaction, Needs Looking forVariations Simultaneously has a significant positive effect on thetransfer of Economics Students brand of the Khairun University,Ternate